EFL Teacher Identity Construction During Online Learning: Challenges, Adaptations, and Pedagogical Implications - Lisa Elvi Wijaya; Concilianus Laos Mbato; Paulus Kuswandono; Barli Bram (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The development of online learning and digital technologies has influenced the formation of EFL teacher identity. This literature review investigates the development of EDL teacher identity during online learning. This review aims to provide a comprehensive understanding of the complexities and subtleties of EFL teacher identity construction in the online learning context. The selected studies were collected through a systematic approach. Thematic analysis was employed to analyze the unique challenges encountered by EFL instructors during online learning, their adaptation and transformation in identity construction, and the pedagogical implications for effective online language teaching. The results emphasized the importance of addressing challenges, supporting EFL teachers in professional development, and implementing effective teaching methods in online language learning. These findings contribute to the improvement of EFL teacher preparation, pedagogical practices, and online learning support systems.